STUDI KRITIS TERHADAP SARANA IBADAH - Kholid Saifulloh (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
Each goal has a means that helps to get to that goal. Likewise worship which is the main purpose of human creation, Allah subhahu wa ta'a he said: